2017
DOI: 10.1111/tmi.12827
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii (Q fever) prevalence in associated populations of humans and small ruminants in The Gambia

Abstract: Coxiella burnetii infection is endemic among both humans and small ruminants in this area of The Gambia. Human and animal exposure to C. burnetii were related at compound level. Further research into the clinical relevance of C. burnetii infection in West Africa is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
1
9
1
Order By: Relevance
“…[20,21,22,31,32,33,34,35,36,37,38,39,40,41,42]; nine reporting on Leptospira spp. [22,26,27,28,43,44,45,46,47]; 13 reporting on Coxiella burnetii [23,24,25,39,40,41,48,49,50,51,52,53,54]; five on Mycobacterium bovis [42,55,56,57,58]; eight on Rickettsia spp. [25,53,54,59,60,61,62,63]; five reporting on Anaplasma spp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[20,21,22,31,32,33,34,35,36,37,38,39,40,41,42]; nine reporting on Leptospira spp. [22,26,27,28,43,44,45,46,47]; 13 reporting on Coxiella burnetii [23,24,25,39,40,41,48,49,50,51,52,53,54]; five on Mycobacterium bovis [42,55,56,57,58]; eight on Rickettsia spp. [25,53,54,59,60,61,62,63]; five reporting on Anaplasma spp.…”
Section: Resultsmentioning
confidence: 99%
“…Five articles probed the presence of Q fever in human and animal hosts [41,48,50,51,52]. Abdel-Moein and Hamza examined vaginal discharges and placental cotyledons from animals that had aborted and found an overall prevalence of 0.9%, with the highest prevalence of Q fever being found in goats (3.4%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have associated livestock production as a significant risk factor for the acquisition of Q fever by humans. Direct evidence was provided in a recent study of small ruminants and humans in Gambia, which identified that the presence of a C. burnetii positive animal in a compound was a significant risk factor in human infection (Bok et al, 2017).…”
Section: Livestock and Human Cross Infectionmentioning
confidence: 99%